PENGELOLAAN PESERTA DIDIK UNTUK MENINGKATKAN MUTU OUTPUT PADA SATUAN PENDIDIKAN KERJA SAMA (SPK) (STUDI KASUS PADA SMA TUNAS BANGSA KUBU RAYA) - Agustin Madjid; Aunurrahman Aunurrahman; Wahyudi Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractManaging students is very important to be implemented at schools in order that the school quality can be improved. The aim of managing students was to manage student activities in order that the activities support the learning process at schools where the learning process can run smoothly, orderly, and regularly to enable students learn optimally. Considering the objectives and benefits of managing the students, the quality of education organisation or schools including Satuan Pendidikan Kerjasama (SPK) try their best to manage their students. The purpose of this study was to obtain descriptive information about the management of students with research aspects about analyzing the needs of prospective students, planning prospective students, recruiting prospective students, selecting prospective students, placing prospective students, and career guidance for students to improve quality output of SMA Tunas Bangsa Kubu Raya as an SPK in West Kalimantan. This study found that the management of students in SMA Tunas Bangsa Kubu Raya was done through aspects of management of students. An analysis of the needs of prospective participants was carried out by the principal with the foundation by considering the ratio of teachers and students. Key words: Management, Quality Output, students